Sickle as Crescent: Islam and Communism in the Netherlands East Indies, 1915-1927 - Hongxuan, Lin (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2018)
This paper examines the confluence of Islam and Communism in the Netherlands East Indies from 1915-1927, by studying how Islam and Communism were theorized as compatible. It analyzes the nature of conciliatory discourses linking Communism and Islam by exploring the profuse anti-colonial print culture of the period. This paper examines four corpora of sources: the published writings of Tan Malaka; selected excerpts from two newspapers edited by Haji Misbach and his associates; Tjokroaminoto’s 1924 book, Islam and Socialism; and finally, Soekarno’s 1926 article, published as Nationalism, Islam and Marxism. This paper will conclude with a brief examination of Dutch reports and oral testimony regarding how Islam and Communism figured in the motivations of participants in the 1926-1927 Communist uprisings.DOI: 10.15408/sdi.v25i2.5675